Increased prevalence of depression and anxiety among adults initiating antiretroviral therapy during the COVID-19 pandemic in Shinyanga region, Tanzania - Solis Winters; Amon Sabasaba; Carolyn A. Fahey; Laura Packel; Emmanuel Katabaro; Yudas Ndungile; Prosper F. Njau; Sandra I. McCoy (AIDS Research and Therapy, 2023)
Abstract Background Concerns about the interconnected relationship between HIV and mental health were heightened during the COVID-19 pandemic. This study assessed whether there were temporal changes in the mental health status of people living with HIV presenting for care in Shinyanga region, Tanzania. Specifically, we compared the prevalence of depression and anxiety before and during COVID-19, with the goal of describing the changing needs, if any, to person-centered HIV services. Methods We analyzed baseline data from two randomized controlled trials of adults initiating ART in Shinyanga region, Tanzania between April-December 2018 (pre-COVID-19 period, n = 530) and May 2021-March 2022 (COVID-19 period, n = 542), respectively. We compared three mental health indicators that were similarly measured in both surveys: loss of interest in things, hopelessness about the future, and uncontrolled worrying. We also examined depression and anxiety which were measured using the Hopkins Symptom Checklist-25 in the pre-COVID-19 period and the Patient Health Questionnaire-4 in the COVID-19 period, respectively, and classified as binary indicators per each scale’s threshold. We estimated prevalence differences (PD) in adverse mental health status before and during the COVID-19 pandemic, using stabilized inverse probability of treatment weighting to adjust for underlying differences in the two study populations. Results We found significant temporal increases in the prevalence of feeling ‘a lot’ and ‘extreme’ loss of interest in things [‘a lot’ PD: 38, CI 34,41; ‘extreme’ PD: 9, CI 8,12)], hopelessness about the future [‘ a lot’ PD: 46, CI 43,49; ‘extreme’ PD: 4, CI 3,6], and uncontrolled worrying [‘ a lot’ PD: 34, CI 31,37; ‘extreme’ PD: 2, CI 0,4] during the COVID-19 pandemic. We also found substantially higher prevalence of depression [PD: 38, CI 34,42] and anxiety [PD: 41, CI 37,45]. Conclusions After applying a quasi-experimental weighting approach, the prevalence of depression and anxiety symptoms among those starting ART during COVID-19 was much higher than before the pandemic. Although depression and anxiety were measured using different, validated scales, the concurrent increases in similarly measured mental health indicators lends confidence to these findings and warrants further research to assess the possible influence of COVID-19 on mental health among adults living with HIV. Trial Registration NCT03351556, registered November 24, 2017; NCT04201353, registered December 17, 2019.